ARTIFICIAL INTELLIGENCE AS CO-AUTHOR: THE AMPLIFYING COGNITIVE AGENT IN SCIENTIFIC PRODUCTION - Marcos Borges Paes, Tadeu; Sergio Souza Borges, Marcos (Journal of Interdisciplinary Debates, 2026)
This article critically analyzes the incorporation of Artificial Intelligence (AI) in scientific production, advocating for its understanding not as an auxiliary tool, but as an amplifying cognitive agent in the development of academic articles and dissertations. It starts from the premise that traditional models of scientific writing, based on individual authorship, textual linearity, and manual elaboration, have become insufficient in the face of contemporary epistemological complexity and informational volume. The approach adopted is theoretical-reflective, grounded in bibliographic review and epistemological analysis, engaging with studies on extended cognition, distributed authorship, and methodological innovation in scientific research. It argues that AI enhances human cognitive capabilities by expanding processes of conceptual organization, critical literature analysis, argumentative structuring, and textual revision, without replacing the intellectual and ethical role of the researcher. It concludes that the conscious adoption of AI as an amplifying cognitive agent represents a structural evolution in the modes of production, validation, and dissemination of scientific knowledge.